Information Integration within the enterprise using XML the XQuery language leverages XML for an effective real-time solution. - Basu, Julie
This article addresses the problem of heterogeneous XML-based information integration within the enterprise. First we examine the business problem and the technology options currently available to build a solution. Next, we discuss how emerging XML-based technologies can be used to effectively solve the problem. Specifically, we show how XQuery in conjunction with a J2EE-based application server can be the basis of a powerful and flexible architecture for synthesizing information in real time from heterogenous sources across the enterprise.